Ethanol stimulates the in vivo axonal movement of neuropeptide dense core vesicles in Drosophila motor neurons - Iacobucci, Gary J (J Neurochem, 2017)
Proper neuronal function requires essential biological cargoes to be packaged within membranous vesicles and transported, intracellularly, through the extensive outgrowth of axonal and dendritic fibers. The precise spatiotemporal movement of these cargoes is vital for neuronal survival and, thus, is highly regulated. In this study we test how the axonal movement of a neuropeptide containing dense core vesicle (DCV) responds to alcohol stressors. We found that ethanol induces a strong anterograde bias in vesicle movement. Low doses of ethanol stimulate the anterograde movement of neuropeptide-DCV while high doses inhibit bidirectional movement. This process required the presence of functional kinesin-1 motors as reduction of kinesin prevented the ethanol-induced stimulation of the anterograde movement of neuropeptide-DCV. Furthermore, expression of inactive GSK-3β also prevented ethanol-induced stimulation of neuropeptide-DCV movement, similar to pharmacological inhibition of GSK-3β with lithium. Conversely, inhibition of PI3K/AKT signaling with wortmannin led to a partial prevention of ethanol-stimulated transport of neuropeptide-DCV. Taken together, we conclude that GSK-3β signaling mediates the stimulatory effects of ethanol. Therefore, our study provides new insight into the physiological response of the axonal movement of neuropeptide-DCV to exogenous stressors.